Age‐related changes in the effects of stress in pregnancy on infant motor development by maternal report: The Queensland Flood Study. Issue 5 (22nd March 2016) - Simcock, Gabrielle; Kildea, Sue; Elgbeili, Guillaume; Laplante, David P.; Stapleton, Helen; Cobham, Vanessa; King, Suzanne
ABSTRACT: The current study examined the effects of a natural disaster (a sudden onset flood) as a stressor in pregnancy on infant fine and gross motor development at 2, 6, and 16 months of age. Whether the timing of the stressor in pregnancy or sex of the infant moderated the impact of the prenatal maternal stress on motor development was also explored. Mothers' objective experiences of the flood, emotional reactions and distress, and their cognitive appraisal of the event were assessed retrospectively. Infants' fine and gross motor skills were assessed with the Ages and Stages Questionnaire, and results showed age‐related changes in the effects of prenatal maternal stress on these domains. At 2 months, higher levels of prenatal maternal stress was positively related to infant motor development, yet at 6 and 16 months of age there was a negative association, particularly if flood exposure occurred later in pregnancy and if mothers had negative cognitive appraisals of the event. Results also showed differential effects of the maternal stress responses to the floods on infants' fine and gross motor development at each age and that infant sex did not buffer these effects. © 2016 Wiley Periodicals, Inc. Dev Psychobiol 58: 640–659, 2016.